Desain E-Modul Program Linear Bernuansa Keislaman dan Kerifan Lokal untuk Mendukung Kemampuan Berpikir Tingkat Tinggi Mahasiswa - Endah Wulantina; Asa Arifah Nusa; Asih Karuniawati (Tapis: Jurnal Penelitian Ilmiah, 2025)
This research aims to: 1) develop a linear program e-module with Islamic nuances and local wisdom to support students' high-level thinking skills; 2) determine students' responses to the module that has been developed. The method used in this research is a design research development study model, consisting of two steps: preliminary design and formative evaluation design. Formative evaluation design consists of self-evaluation, prototyping (expert validation tests, individual trials, and small group trials), as well as field trials. The research subjects were 35 mathematics education students. Data collection techniques consisted of questionnaires and tests. This research produced a valid and engaging e-module to support students' higher-order thinking skills. Student responses to the developed e-module were interesting. The development of this linear programming e-module with Islamic nuances and local wisdom offers an alternative solution to support higher-order mathematical thinking skills.